2019
DOI: 10.4103/psychiatry.indianjpsychiatry_194_18
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-Methyltransferase Val158Met and brain-derived neurotrophic factor Val66Met gene polymorphisms in paraphilic sexual offenders

Abstract: Background: Child sexual abuse (CSA) is an important problem worldwide. The reason of sex abuse is considered as multifactorial. Genetic contribution reported by recent studies is a significant evidence for this pathologic behavior. Catechol-O-Methyltransferase (COMT) is an enzyme in the metabolic inactivation of catecholamine and substances containing catecholamines such as dopamine, epinephrine, and norepinephrine. COMT polymorphism causes functional changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Studies in local and abroad have shown that the changes of pain-related genes in the trigeminal ganglion are closely related to the occurrence and development of tooth movement pain [ 28 , 29 ]. COMT is mainly distributed in the postsynaptic neurons and glial cells of the nervous system [ 30 , 31 ], as well as in the peripheral tissues [ 32 ]. In addition, Nicholson et al found that the COMT gene expression level in the trigeminal ganglion will lead to corresponding changes in the behavioral response of pain in experimental animals [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in local and abroad have shown that the changes of pain-related genes in the trigeminal ganglion are closely related to the occurrence and development of tooth movement pain [ 28 , 29 ]. COMT is mainly distributed in the postsynaptic neurons and glial cells of the nervous system [ 30 , 31 ], as well as in the peripheral tissues [ 32 ]. In addition, Nicholson et al found that the COMT gene expression level in the trigeminal ganglion will lead to corresponding changes in the behavioral response of pain in experimental animals [ 33 ].…”
Section: Discussionmentioning
confidence: 99%